Maternity and Paternity Leave Policy in Indonesia: A Study on United Nations Development Indonesia - Fathia Alya Shabrina; Fibria Indriati (Journal of Social Research, 2023)
Industrial relations today strongly prioritise work diversity, where gender equality in the work environment is one of its essential aspects. One way of gender equality is through the provision of maternity leave and paternity leave for female and male workers. Indonesia has a legal basis that governs both policies. However, the policy does not yet cover other aspects of working life. UNDP Indonesia as an organization under the auspices of the United Nations has regulations regarding two maternity leave policies as an effort to equalise gender, and it describes in detail what workers get. The difference between the two is very significant, as can be seen from the points of work conditions, the provisions for the time to take leave, and the right to breastfeed and bring children to the office. Granting these rights can help workers' physical and mental health. The granting of this leave entitlement can also help organisations to reduce turnover rates. For this reason, Indonesia can follow the aspects discussed by UNDP for further legal studies to prosper its workers and organisations in Indonesia.